Special paperPercutaneous angioplasty of the only patent renal artery – treatment of choice for end-stage heart failure - Kądziela, Jacek; Tyczyński, Paweł; Michałowska, Ilona; Konka, Marek; Duda, Bartosz; Witkowski, Adam (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
The causes leading to the exacerbation of preexisting chronic heart failure can be various. Renal artery stenosis is an important cause of renal dysfunction, and can lead to worsening of heart failure and increased mortality. We present a 49-year old male patient after acute myocardial infarction, heart failure with left ventricle ejection fraction of 20%, permanent atrial flutter, peripheral vascular disease, chronic kidney disease and arterial hypertension. In 2008 the patient underwent stenting of the left renal artery. At that time there was only discrete stenosis of the right renal artery. Two years later the patient presented with exacerbation of bi-ventricular chronic heart failure and renal failure. The echocardiography revealed dramatically reduced systolic function of both ventricles. As no response to intravenous diuretics was achieved, the patient underwent several courses of hemodialysis. Before considering the patient as a potential candidate for orthotopic heart transplantation, color Doppler ultrasound showed the occlusion of the left renal artery and significant stenosis of the right renal artery, which was stented. After the procedure spectacular clinical improvement was observed. The results of two randomized trials, ASTRAL and STAR, were discouraging for invasive treatment of renal artery stenosis. Still, serious doubts regarding the methodology of the studies were raised. Renal artery stenting may be the treatment of choice in highly selected patients and lead to clinical improvement.